2015
DOI: 10.2147/ott.s93297
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of serum interleukin-6 expression in colorectal cancer: a systematic review and meta-analysis

Abstract: PurposeInterleukin-6 (IL-6) plays an important role in human colorectal cancer (CRC) development. However, the exact clinical and prognostic significance of IL-6 in CRC is still unclear. Here, we conducted this meta-analysis to explore this issue in detail.MethodsA meta-analysis was performed to clarify the association between serum IL-6 expression and clinical outcomes in articles published up to June 2015. Weighted mean difference (WMD) and its corresponding 95% confidence interval (CI) were used to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
2
15
2
Order By: Relevance
“…[19][20][21][22] IL-6 levels are correlated with CRC development, tumor cell invasion, increased distant metastasis and decreased survival time. 23,24 In mouse models of CRC, ablation of IL-6 reduces tumor burden and increases survival time, suggesting it is a critical tumor-promoting factor. 25 The combination of TNF-a and IL-6 produces a synergistic response in CRC that promotes proliferation, survival and further cytokine production.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] IL-6 levels are correlated with CRC development, tumor cell invasion, increased distant metastasis and decreased survival time. 23,24 In mouse models of CRC, ablation of IL-6 reduces tumor burden and increases survival time, suggesting it is a critical tumor-promoting factor. 25 The combination of TNF-a and IL-6 produces a synergistic response in CRC that promotes proliferation, survival and further cytokine production.…”
mentioning
confidence: 99%
“…IL‐1β signaling in many cell types, including epithelial cells, fibroblasts and infiltrating immune cells, results in production of IL‐6 and TNF‐α . IL‐6 levels are correlated with CRC development, tumor cell invasion, increased distant metastasis and decreased survival time . In mouse models of CRC, ablation of IL‐6 reduces tumor burden and increases survival time, suggesting it is a critical tumor‐promoting factor .…”
mentioning
confidence: 99%
“…IL-6, a pleiotropic pro-inflammatory Th2 cytokine, has been demonstrated by several studies to participate in tumor cell proliferation, apoptosis and angiogenesis (21,22). It was also reported that high IL-6 expression in patient plasma was associated with shorter OS in lung (23) and colorectal cancer (24). In addition, IL-6 alone was found to be significantly associated with PFS in the TG4010 study.…”
Section: Discussionmentioning
confidence: 89%
“…Two cytokines with a more established prognostic role in colorectal cancer are IL-6 and IL-8 and whilst these cytokines were included in the majority of panels tested, they were only identified as independent predictors in two of the studies (49,50). Given the high level of co-variance between many cytokines, one explanation may be that individual cytokines negate each other in multi-variate analysis.…”
Section: Discussionmentioning
confidence: 99%